Between Evidence and Identity: Rethinking the Modern Predicament of Acupuncture Anesthesia from an Epistemic Perspective - Rilin ZHANG; Changle WU; Xintong YU; Ke WANG; Jia ZHOU (Chinese Medicine and Culture, 2026)
Abstract Acupuncture anesthesia (AA) is widely recognized as a notable achievement within the realm of integrative medicine; however, its advancement remains limited despite increasing scientific interest and expanding clinical research. This article reevaluates the contemporary challenges faced by AA from an epistemic standpoint, positing that these challenges stem not primarily from a lack of efficacy but from an inherent structural tension between evidence-based evaluation and cross-cultural medical reasoning. By drawing upon medical history, the philosophy of medicine, and studies in traditional Chinese medicine (TCM), we illustrate that methodological incompatibilities within current evidence hierarchies, alongside divergent cognitive frameworks, collectively influence the scientific assessment, clinical application, and international discourse surrounding AA. Instead of perceiving these tensions as irreconcilable conflicts between traditional and modern medicine, we propose that they represent differences in the organization, interpretation, and legitimization of medical knowledge across distinct epistemic traditions. Building on this analysis, the paper delineates three complementary pathways: the development of evidence architectures that align with the systemic logic of TCM, the enhancement of interdisciplinary education and collaborative clinical practice, and the reconstruction of international communication through value-oriented dialogue. Collectively, these strategies are designed not to integrate AA into conventional biomedical paradigms, but rather to establish more inclusive evaluative frameworks that can accommodate diverse forms of medical knowledge. Consequently, the experience of AA serves as a broader model for reconciling evidence, cultural identity, and epistemic pluralism within the context of the modernization and globalization of traditional medicine.